+0  
 
0
78
1
avatar+467 

help please

 Dec 8, 2020
 #1
avatar+114221 
+1

 

f(0)  = a/2

 

To find the inverse :

 

y =  a  / (x + 2)         get x by itself

 

y ( x + 2)  = a

 

xy  + 2y  =  a

 

xy  = a - 2y  

 

x =  (a -2y)  / y   swap x and  y

 

y = (a - 2x ) / x    =  the inverse to f(x)

 

f-1 (3a)  =   (a -2(3a) ) / (3a)  =  -5a/ 3a   =  -5/3

 

Therefore

 

f(0)  = f-1 (3a)    gives us

 

a/2  =  -5/3

 

a = 2 (-5/3)  =  -10/3

 

 

 

cool cool cool

 Dec 8, 2020

35 Online Users